The extracellular matrix factsbook - Ayad, Shirley (Factsbook series., 1998)
The Second Edition of The Extracellular Matrix FactsBook has been completely revised, updated and expanded by over 50 percent. It contains over 85 entries on the diverse group of macromolecules that assemble toform the extracellular matrix. Entries provide information on molecular structure, isolation, primary structure, structural and functional sites, gene structure, database accession numbers, and key references. Key Features * Compiled by members of one of the foremost centers of matrix biochemistry in the world * Contains over 30 new entries, with all previous entries being revised and updated * Includes new entries on proteinases involved in the deposition of the extracellular matrix * Presents 3D ribbon diagrams in cases where the protein structure is now known.